Pola Komunikasi Pelayanan Customer Service Bank Jabar-Banten Selama Pandemi Covid-19 - Agia Dwi Vici Utami; Dasrun Hidayat; Suci Nujiana; Mega Mutia Maeskina (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2022)
This study focuses is changing the way of Customer Service works during the Covid-19 pandemic. The change in the Customer Service mechanism during the Covid-19 pandemic became the background of the problem, therefore a study was needed regarding the working mechanism of Customer Service during the Covid-19 pandemic. The purpose of the study was to analyze all forms of change and communication patterns in Customer Service services during the Covid-19 pandemic. The qualitative method used in this research is a case study approach. Involving two Customer Service and three customers as informants. The data collection techniques are data reduction, data presentation and conclusions (data verification). The results of this study found three differences in the mechanism of Customer Service during the Covid-19 pandemic which included changes in the layout of the room, changes in working hours and Customer Service attributes. The results of this study, researchers hope to contribute to improving the business of the banking sector and improve Customer Service hence that there is no miscommunication does not occur in the next time.